PENGARUH SHIFT KERJA TERHADAP TINGKAT KELELAHAN KERJA DAN DAMPAKNYA TERHADAP KINERJA OPERATOR PRODUKSI ARV PT KIMIA FARMA (PERSERO) TBK. UNIT PLANT JAKARTA - Auliya, Nurul (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
This final assignment aimed to know the influance of work shifting on fatigue and its impact on performace of ARV Production Operators. Work shifting is work period that determined by company and devided into three times (morning, evening, and night). Work Shifting has applied to support production activities and provided customer service optimally. Fatigue is abnormality feeling, tired, weak, uncontrol, and other feelings that difficult to defined, because fatigue is subjective feelings. This research used primary and secondary data. The primary data is schedule work and the secondary data is qestionnaire respon to measured work fatigue and work performance. This data analyzed using path analysis. Based on analysis proved that work shifting, fatigue, and perfomance has no influences with F arithmetic amounted to 3.34 > F tabel 1.189 which mean work shifting has no influences on fatigue and performance.